Drug Trafficking in Afghanistan - Shafiullah Farzayee (Department of Political Science - Universitas Sains Al-Qur’an, 2020)
In the contemporary history of Afghanistan, opium cultivation brought revenues to the people. Yet, the cultivation and drug trafficking has been associated with terrorism in recent days. The fact that many insurgency groups yield incomes from the trafficking is undeniable. Moreover, not only does it become domestic issues, but it also gains concerns in the regional level. This paper explains its development in the context of Afghanistan and the alternative solution. In this case, this study proposes Saffron as a substitution to opium that the government could consider to take.